2017
DOI: 10.1007/s11064-017-2414-6
|View full text |Cite
|
Sign up to set email alerts
|

CB1 Receptors Mediated Inhibition of ATP-Induced [Ca2+]i Increase in Cultured Rat Spinal Dorsal Horn Neurons

Abstract: Spinal cannabinoid receptor 1 (CBR) and purinergic P2X receptors (P2XR) play a critical role in the process of pathological pain. Both CBR and P2XR are expressed in spinal dorsal horn (DH) neurons. It is not clear whether CB receptor activation modulates the function of P2X receptor channels within dorsal horn. For this reason, we observed the effect of CP55940 (cannabinoid receptor agonist) on ATP-induced Ca mobilization in cultured rat DH neurons. The changes of intracellular calcium concentration ([Ca]i) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Similarly, cannabinoid inhibits ATP‐induced currents and calcium influx through G i/o protein‐coupled CB1 cannabinoid receptors and AC‐cAMP‐PKA signaling pathway in rat trigeminal ganglionic neurons and cultured spinal dorsal horn neurons. 42 , 43 In addition, intracellular application of BAPTA, a chelator of calcium ions, failed to reverse the inhibitory effect of DEX on α,β‐meATP‐induced currents, suggesting no involvement of intracellular Ca. 2 +…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cannabinoid inhibits ATP‐induced currents and calcium influx through G i/o protein‐coupled CB1 cannabinoid receptors and AC‐cAMP‐PKA signaling pathway in rat trigeminal ganglionic neurons and cultured spinal dorsal horn neurons. 42 , 43 In addition, intracellular application of BAPTA, a chelator of calcium ions, failed to reverse the inhibitory effect of DEX on α,β‐meATP‐induced currents, suggesting no involvement of intracellular Ca. 2 +…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic effect of CB1 receptor activation is mediated by a negative modulation of the P2X 3 receptor in the primary afferent neurons in carrageenan-induced inflammatory pain in mice [12]. In cultured dorsal spinal neurons, the opening of P2X receptor channels is down-regulated by activation of cannabinoid CB1 receptor [13]. Our previous studies indicated that CB2 receptor activation produces a pronounced inhibition of CCI-induced thermal hyperalgesia and significantly inhibited the increased expression of P2Y 12 and P2Y 13 receptors, which open up the possibility that P2Y 12 and P2Y 13 receptor expression are down-regulated by CB2 receptor activation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In cultured dorsal spinal neurons, the opening of P2X receptor channels is down-regulated by activation of cannabinoid CB1 receptor [13]. Our previous studies indicated that CB2 receptor activation produces a pronounced inhibition of CCI-induced thermal hyperalgesia and significantly inhibited the increased expression of P2Y 12 and P2Y 13 receptors, which open up the possibility that P2Y 12 and P2Y 13 receptor expression are down-regulated by CB2 receptor activation [11]. Based on these reports, we hypothesized that the expression of P2X 4 and P2X 7 receptor in dorsal spinal cord may be also influenced after CB2 receptor activation in neuropathic pain rats.…”
Section: Introductionmentioning
confidence: 99%